Analysis of Oil and Gas Ethane and Methane Emissions in the Southcentral and Eastern United States Using Four Seasons of Continuous Aircraft Ethane Measurements. Issue 10 (25th May 2021) - Barkley, Z. R.; Davis, K. J.; Feng, S.; Cui, Y. Y.; Fried, A.; Weibring, P.; Richter, D.; Walega, J. G.; Miller, S. M.; Eckl, M.; Roiger, A.; Fiehn, A.; et al.
Abstract: In the last decade, much work has been done to better understand methane (CH4 ) emissions from the oil and gas (O&G) industry in the United States. Ethane (C2 H6 ), a gas that is co‐emitted with thermogenic sources of CH4, is emitted in the US predominantly by the O&G sector. In this study, we perform an inverse analysis on 200 h of atmospheric boundary layer C2 H6 measurements to estimate C2 H6 emissions from the US O&G sector. Measurements were collected from 2017 to 2019 as part of the Atmospheric Carbon and Transport (ACT) America aircraft campaign and encompass much of the central and eastern United States. We find that for the fall, winter, and spring campaigns, C2 H6 data consistently exceeds values that would be expected based on EPA O&G leak rate estimates by more than 50%. C2 H6 observations from the summer 2019 data set show significantly lower C2 H6 enhancements in the southcentral region that cannot be reconciled with data from the other three seasons, either due to complex meteorological conditions or a temporal shift in the emissions. Combining the fall, winter, and spring C2 H6 posterior emissions estimate to an inventory of O&G CH4 emissions, we estimate that O&G CH4 emissions are larger than EPA inventory values by 48%–76%. Uncertainties in the gas composition data limit the accuracy of using C2 H6 as a proxy for O&G CH4 emissions. These limits could be resolved retroactively by increasing the availability of industry‐collected gas composition data. Plain Language Summary: Methane is a potent greenhouse gas responsible for a quarter of the warming the climate has experienced thus far. The oil and gas (O&G) sector is a significant source of methane through leaks in its infrastructure. Recent studies of individual basins have found emissions from O&G in the US to be greater than inventory estimates, but difficulties arise with source attribution in broader scale studies due to the numerous potential sources of methane. This study quantifies methane emissions from O&G by looking at atmospheric ethane, a gas whose emissions originate mostly from O&G in the US. Hundreds of hours of boundary layer ethane observations were collected via aircraft over the course of four seasons between 2017 and 2019. These observations are compared with model‐projected ethane values based on our current knowledge of ethane emissions, and those emissions are adjusted to best match the observed data. We find ethane emissions are grossly underestimated in the US. Because ethane is co‐emitted with O&G methane sources, this underestimation of ethane reflects similar underestimations in O&G methane emissions. We conclude that US inventories are underestimating methane emissions from O&G by 48%–76%. Key Points: This study uses ethane observations to quantify both ethane and methane emissions from the United States oil and gas (O&G) sector Ethane emissions in the southcentral and eastern United States are larger than the NEI 2017 inventory by more than a factor of 2 Ethane results indicate that the US EPA methane inventory is underestimating leak rates from the O&G sector